Laparoscopic common bile duct exploration after failed endoscopic retrograde cholangio-pancreatography: Our patient series over a period of 10 years - Arun M Bhardwaj; Kamal K Trehan; Vishwas Sharma (Journal of Minimal Access Surgery, 2022)
Aim: Laparoscopic CBD exploration (LCBDE) for Common bile duct (CBD) stones with laparoscopic cholecystectomy (LC) is an alternative to open CBD exploration, in patients with failed endoscopic retrograde cholangio-pancreatography (ERCP). It is being performed at few centres with adequate surgical expertise. Herein, we present our experience of LCBDE with LC over a period of 10 years. Patients and Methods: A retrospective analysis of prospectively recorded data of 121 consecutive patients was performed from February 2010 to November 2019, who underwent LC and LCBDE by choledochotomy in a single surgical unit. These included all patients with failed pre-operative ERCP. Results: Out of 121 patients, LCBDE successfully cleared the CBD in 118, and three patients were converted to open surgery. All these patients underwent choledochotomy for adequate exploration of CBD. T-tube closure of CBD was performed in 103 patients and removed after a mean of 14.6 ± 2.4 days. Primary closure was performed in 15 patients. The mean hospital stay post-procedure was 3.4 ± 0.7 days. Complete ductal clearance was achieved in 115 patients, and residual stone fragments reported in three patients were removed by ERCP. None of the patients experienced biliary peritonitis, biliary fistula, pancreatitis or cholangitis. There was no 30-day mortality and no recurrent stones reported with a mean follow-up of 12.4 ± 3.9 months. Conclusion: With adequate surgical expertise, LCBDE is a feasible alternative to open surgery for CBD stones after failed ERCP with early recovery and low morbidity.